2012
DOI: 10.1590/s0100-204x2012000700018
|View full text |Cite
|
Sign up to set email alerts
|

Carbono do solo e atributos de fertilidade em resposta à calagem superficial em plantio direto

Abstract: Resumo -O objetivo deste trabalho foi avaliar o efeito da aplicação de calagem superficial sobre o conteúdo de carbono orgânico total (COT) do solo, em plantio direto, e identificar a relação entre esse conteúdo e outros atributos de fertilidade. O experimento foi realizado em Latossolo Vermelho de textura média, em Ponta Grossa, PR. Os tratamentos consistiram da aplicação de calcário dolomítico na superfície do solo, nas doses 0 e 6 Mg ha -1 , em 1993, e da reaplicação de 0 e 3 Mg ha -1 , em 2000, nas parcela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 25 publications
2
6
0
3
Order By: Relevance
“…The previous results are corroborated by those obtained by Ebeling et al (2011), Briedis et al (2012, and Matias et al (2015), who found a positive correlation between organic carbon (or organic material) and the cation exchange capacity (CEC), where carbon is the main contributor to the increase in the CEC and the increase in nutrient adsorption.…”
Section: Spatial Distributionsupporting
confidence: 69%
“…The previous results are corroborated by those obtained by Ebeling et al (2011), Briedis et al (2012, and Matias et al (2015), who found a positive correlation between organic carbon (or organic material) and the cation exchange capacity (CEC), where carbon is the main contributor to the increase in the CEC and the increase in nutrient adsorption.…”
Section: Spatial Distributionsupporting
confidence: 69%
“…Rodrighero et al, (2015), when evaluating the superficial application under no-tillage system, where an improvement of Mg contents were observed in the soil profile, due to the formation of MgSO4 0 complex, which has high mobility in the soil. Similar results were also found by Briedis et al, (2012), when evaluating areas under no-tillage systems observed improvements in this attribute in the topsoil, with reduction as depth was increased. Regardless of the gypsum dose, the application of limestone promoted a slight increase in the CEC in the topsoil (0-20 cm); however at the 20-40 cm depth, no significant effect of the application of these inputs (Figures 3a, 3b) was observed.…”
Section: First Agricultural Cyclesupporting
confidence: 85%
“…With increasing lime dose, decreasing ΔpH values were observed. However, this result does not necessarily imply that increasing lime dose decreased soil CEC, in contrast the majority of authors (Alleoni et al, 2005;Santos et al, 2010;Briedis et al, 2012;Calonego et al, 2012). This finding is due to the short period of time (180 days) allowed for lime hydrolysis before soil sampling and subsequent analysis.…”
Section: δPh and Ph Pzcmentioning
confidence: 85%